Using performance assessment to assess and develop understanding of probability - Khalid, Madihah; Harun, Zurina (2012)
With the emphasis on assessment for learning (AFL) in the mathematic curriculum of the New Education System for the 21st Century (SPN 21) in Brunei, teachers have been trying their best to incorporate assessment and learning together in a well-designed mathematics lesson. Performance assessment is seen as one of the approaches that will encourage teachers to implement AFL and this study was conducted and evaluated to determine the effectiveness of performance - base assessment in student’ motivation to learn and understand probability . The task – ‘ The Horse Race Activity ’, was chosen in helping teachers to examine students’ thinking, reasoning, communication and team-work during the learning process . The result of this activity was encouraging. It was found that the activity made students interested in the lesson and topic; students were able to explain and reason mathematically though not very effectively; but were still not proficient enough in relating theory learned with real-world task. However, the research was able to convince other teachers of the advantages of performance assessment in teaching and learning generally and in probability particularly .